2011
DOI: 10.1080/01635581.2011.538485
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Triggers Apoptosis Through Regulating Ceramide Metabolizing Genes in Human K562 Chronic Myeloid Leukemia Cells

Abstract: Resveratrol, an important phytoalexin in many plants, has been reported to have cytotoxic effects on various types of cancer. Ceramide is a bioactive sphingolipid that regulates many signaling pathways, including cell growth and proliferation, senescence and quiescence, apoptosis, and cell cycle. Ceramides are generated by longevity assurance genes (LASS). Glucosylceramide synthase (GCS) and sphingosine kinase-1 (SK-1) enzymes can convert ceramides to antiapoptotic molecules, glucosylceramide, and sphingosine-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 31 publications
0
32
0
Order By: Relevance
“…Inhibition of GCS and SK1 triggered apoptosis via leading to ceramide accumulation in imatinibresistant and imatinib-sensitive K562 CML cell lines [209]. Additionally, when we treated K562 human CML cell lines and HL60 human acute pro-myelocytic leukemia cell lines with resveratrol in combination with ceramide analog, GCS inhibitor, or SK1 inhibitor, apoptotic effects of resveratrol increased synergistically in the cells treated with resveratrol and ceramide combination, while the cells treated with resveratrol and GCS or SK1 combinations resisted to apoptosis as compared to the control group [210,211]. Furthermore, our studies also showed that GCS and SK1 inhibition in combination with nilotinib or dasatinib treatment synergistically triggers apoptosis in K562 and Meg01 human CML cell lines [212,213].…”
Section: Bioactive Sphingolipids In Apoptotic Pathwaysmentioning
confidence: 96%
“…Inhibition of GCS and SK1 triggered apoptosis via leading to ceramide accumulation in imatinibresistant and imatinib-sensitive K562 CML cell lines [209]. Additionally, when we treated K562 human CML cell lines and HL60 human acute pro-myelocytic leukemia cell lines with resveratrol in combination with ceramide analog, GCS inhibitor, or SK1 inhibitor, apoptotic effects of resveratrol increased synergistically in the cells treated with resveratrol and ceramide combination, while the cells treated with resveratrol and GCS or SK1 combinations resisted to apoptosis as compared to the control group [210,211]. Furthermore, our studies also showed that GCS and SK1 inhibition in combination with nilotinib or dasatinib treatment synergistically triggers apoptosis in K562 and Meg01 human CML cell lines [212,213].…”
Section: Bioactive Sphingolipids In Apoptotic Pathwaysmentioning
confidence: 96%
“…The apoptosis in SW-872 human liposarcoma cells induced by quercetin was mediated through the activation of caspase-3, Bax, and Bak and then cleavage of PARP and downregulation of Bcl-2. 12 Kim et al showed that antiproliferative effect of quercetin is mediated via inhibition of PI-3 kinase in cancer cells. 24 Our results revealed that resveratrol treatment induced a dose-dependent increase in the percentage of cells in G0/G1 phase, which was accompanied by a corresponding reduction in the percentage of cells in S phase.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Resveratrol has been shown to induce apoptosis in a variety of cancers such as chronic myeloid leukemia (CML), acute myeloid leukemia (AML), breast, prostate, colon and lung cancers. [11][12][13] The exact mechanism of resveratrol mediated anticancer effect is not fully identified.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Resveratrol aglycone has been reported to have anticancer and chemosensitizing activities against cancer cells; mechanisms of action for this have previously been proposed (1,(25)(26)(27)(28). Anticancer mechanisms of action for resveratrol, which have been described predominantly from in vitro studies, include the inhibition of transcription factors, kinases and other molecules involved in cell proliferation and survival.…”
Section: Discussionmentioning
confidence: 99%